Lingkungan Sekolah Berpengaruh Terhadap Perilaku Merokok Remaja Tunagrahita di SLB Negeri 2 Yogyakarta - Pramesti, Olifia; Riyadi, Sujono (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: Smoking behavior has become increasingly popular lately, including among teenagers. Early adolescents usually like to imitate and try because there is encouragement and support from their surroundings such as the school environment and family environment, as is the case with adolescents with mental retardation. The condition of adolescents who smoke can harm themselves and others who are near them. Many warnings about the dangers of smoking are found in advertisements television and even on cigarette packs. Purpose: To determine the relationship between the school environment and smoking behavior in mentally retarded adolescents as SLB Negeri 2 Yogyakarta. Methods: This research is a type of quantitative research, with a correlation design using a cross-sectional design. Data collection was carried out in April 2023. The population in this study 30 students consisting of SMP and SMA. The research sample 30 students with a total sampling technique. Measuring tools used in the form of school environment questionnaires and smoking behavior questionnaires. Bivariate analysis using lambda test. Result: The results show that school environment had an effect of 96,7% and positive smoking 83,3%. Lambda test results obtained p value of 0,000. Conclusion: There is a correlation between school environment and smoking behavior in mentally retarded adolescents as SLB Negeri 2 Yogyakarta.